Rāṛhera mantrayāna - Siṃha, Mānika Lāla (Ci. Dāśagupta : prātisthāna Baṅgiya Sāhitya Parishaṯ, Bishṇupura Sākhā, 1979)
On the esoteric chants (mantras) of Tantric Buddhism as used in the folk religion of West Bengal.